Representing Prosperity Gospel in South African News Media: A Discursive Reading - Khanyile, Sphesihle B. (Commercialisation of Religion in South Africa: A Pentecostal Approach, 2023)
The discourse of prosperity gospel has attracted significant international research attention. However, contextually, recent South African writings on both mainstream news media and scholarly have associated the prosperity discourse with nefarious and crass acts tantamount to the commercialisation of religion, subsequently birthing a commission of inquiry in South Africa. Prosperity gospel agents, often neo-Pentecostal religious elites, have been reported to weaponise the prosperity message for self-vested commercial gains. Evidently, there appears to exist a nexus between prosperity gospel and the commercialisation of religion, erroneously attracting interchangeable naming and conceptualisation. The chapter acknowledges and foregrounds this nexus but zooms specifically on how the prosperity gospel message represents on select South African English newspaper reports and opinion pieces, appraising the fact that news is never neutral but ideologically charged. Teun van Dijk’s ideological discourse analysis approach is employed to gauge how prosperity gospel is represented from the year 2000–2022 time frame. Emergent ideological themes demonstrate that the representations of prosperity gospel have evolved overtime; from temperate to scathing, attributable to the recent eruptions of commercialised religion manifest in the South African public sphere. Prosperity gospel, a discourse and message of human flourishing is postured by most news authors and opinion piece writers as a practice of commercialisation of religion without considering the nuanced conceptions of the prosperity gospel among both clerics and congregants.
paid